2014
DOI: 10.3390/agronomy5010001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Boron Fertilization of Fine Textured Soils on Corn Yields

Abstract: Boron (B) is an essential micronutrient needed for normal plant growth and development. To evaluate the response of corn to foliar B applications at V4-V6 (4-6 leaves with visible collars) and VT (tasseling) growth stages on fine textured soils, a field experiment was conducted at four sites from 2008 to 2010 in Northeast Missouri. The treatments included a non-treated control; V4-V6 applied B at 0.56, 1.12 and 2.24 kg·ha −1 ; and VT applied B at 0.28, 0.56 and 1.12 kg·ha −1 . Foliar B, applied at V4-V6 at 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…Two boron‐based products (Biopaste and Bioshield) containing 5% BA significantly reduced Eutypa dieback ( E. lata ) on grapevines by 78% to 98% in field trials (Rolshausen & Gubler, ) and the boron‐containing products Biopaste and Gelseal, as well as BA, provided effective control of E. lata when applied to the pruning wound on grapevines (Pitt et al, ; Sosnowski, Loschiavo, Wicks, & Scott, ). On corn, foliar applications of boron at 2.24 kg/ha reduced severity of grey leaf spot compared with the non‐treated control in field experiments (Kaur & Nelson, ). Similarly, foliar application of boron (as H 3 BO 3 , at 6.25 mg/L of boron) decreased the number of leaf lesions and severity of tan spot caused by Drechslera tritici‐repentis in winter durum wheat, especially at the booting stage, because boron was involved in physiological and biochemical effects in plants (Simoglou & Dordas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two boron‐based products (Biopaste and Bioshield) containing 5% BA significantly reduced Eutypa dieback ( E. lata ) on grapevines by 78% to 98% in field trials (Rolshausen & Gubler, ) and the boron‐containing products Biopaste and Gelseal, as well as BA, provided effective control of E. lata when applied to the pruning wound on grapevines (Pitt et al, ; Sosnowski, Loschiavo, Wicks, & Scott, ). On corn, foliar applications of boron at 2.24 kg/ha reduced severity of grey leaf spot compared with the non‐treated control in field experiments (Kaur & Nelson, ). Similarly, foliar application of boron (as H 3 BO 3 , at 6.25 mg/L of boron) decreased the number of leaf lesions and severity of tan spot caused by Drechslera tritici‐repentis in winter durum wheat, especially at the booting stage, because boron was involved in physiological and biochemical effects in plants (Simoglou & Dordas, ).…”
Section: Discussionmentioning
confidence: 99%
“…The surface irrigation is used traditionally at this area which could cause boron leaching (Hall, 2008). Limit crop production was reported due to boron deficiency (Kaur and Nelson, 2015;Haytova, 2013). Boron requirements for vegetables are more than in the other crops (Dursun, 2010), and may increase production efficiency and quality (Haytova, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nawaz et al (2017) stated that fresh and dry matter yield of sorghum were increased with increases in boron doses. Kaur and Nelson (2015) indicated that the highest grain yields obtained at 2.24 kg ha -1 boron application at V4-V6 growth stage of maize. Also, Konuskan (2018) reported that boron applications enhanced grain yield of maize at early vegetative growth stages.…”
Section: Resultsmentioning
confidence: 93%
“…Boron applications can increase maize yield with low quantities (Güneş et al, 2011). Various studies were performed on boron effects on grain yield of maize, previously (Aref, 2011; Kaur and Nelson, 2015;Horuz and Özcan, 2017;Konuskan et al, 2017, Wasaya et al, 2017Nelson and Meinhardt, 2011). However, insufficient researches were performed on boron effects on hay and silage yields and qualities of maize.…”
Section: Introductionmentioning
confidence: 99%